Influence of surfactants on structural, morphological, optical and antibacterial properties of SnO2 nanoparticles. Issue 9 (11th October 2019) - Karuppiah, Sujatha; Thangaraj, Seethalakshmi; Arunachalam Palaniappan, Sudha; Olapalayam Lakshmanan, Shanmugasundaram
Abstract : Tin oxide (SnO2 ) nanoparticles were synthesised using various surfactants of different charges (n‐cetyl trimethyl ammonium bromide, sodium dodecyl sulphate and TRITON X‐100) by the co‐precipitation method. The synthesised nanomaterials were characterised using different techniques to study their structural, surface morphological, optical and anti‐bacterial activities. X‐ray diffraction patterns revealed the formation of a tetragonal rutile structure in pure and surfactants‐aided SnO2 nanoparticles and the results show good agreement with JCPDS data [41‐1445]. The crystallite size of SnO2 nanoparticles was found to decrease with the addition of surfactants. Scanning electron microscopy images exhibit spherical shape morphology with an average diameter of 30–75 nm for pure and surfactants‐aided SnO2 nanoparticles. The band gap energy of the prepared materials was estimated from the UV–visible absorption spectra and a considerable increase in band gap energy was observed in surfactants‐aided SnO2 nanoparticles (3.487, 3.57, 3.50 and 3.3 eV). The antibacterial activities of the synthesised nanoparticles were studied against Escherichia coli and Staphylococcus aureus bacteria.